Rose and the Burma Sky - Amaka,Rosanna; Amaka,Rosanna (Doubleday: [S.l.], 2023)
"1939: In a village in south-east Nigeria on the brink of the Second World War, young Obi watches from a mango tree as a colonial army jeep speeds by, filled with soldiers laughing and shouting, their buttons shining in the sun. To Obi, their promise of a smart uniform and regular wages is hard to resist, especially as he has his sweetheart Rose to impress and a family to support. Years later, when Rose falls pregnant to another man, his heart is shattered. As the Burma Campaign mounts, and Obi is shipped out to fight, he is haunted by the mystery of Rose's lover. When his identity comes to light, Obi's devastation leads to a tragic chain of unexpected events."--Publisher
Keywords: Fiction of Black and Asian Interest